Pelatihan Membangun Jiwa Leadership di Kalangan Santri Pondok Pesantren Al-Furqon Al-Islami Driyorejo - Nurhasan Nurhasan; Nur Salsabila Rhesa; Muhammad Kharis Fajar (Lembaga Pengembangan Kinerja Dosen, 2026)
In the Islamic boarding school, it is hoped that it can prepare students who are resilient to face global developments in the era of the 4.0 revolution which is increasingly rapid, ambiguous and full of uncertainty. Students must be able to adapt in the face of increasingly rapid global developments and are required to be able to balance worldly skills and the hereafter. To be able to compete in global competition, students are not only taught Islamic sciences but also have leadership skills. Leadership is one of the important factors for the success of an organization. Leadership is the art of influencing others, both in relation to individuals and groups. The ability to influence is closely related to the ability of a leader to influence his members to be able to work together in achieving organizational goals. The spirit of leadership cannot appear automatically but must always be honed, especially among teenagers. With the training to build a leadership spirit among the students of the Al-Furqon Al-Islami Driyorejo Islamic Boarding School, it is hoped that they will be able to play a role in channeling energy and developing the potential of the students in a positive direction, one of which is related to the growth and development factor of the leadership spirit so that this is one of the good provisions when they enter the community one day.